TIPE PASANG SURUT DI PELABUHAN BENOA BALI DENGAN METODE ADMIRALTY BERDASARKAN DATA AUTOMATIC WEATHER STATION (AWS) - Hikmah, Diana; Arisanti, Luh Eka; Irmawan, Decky (Jurnal Widya Climago, 2020)
Benoa Port is the main port in Bali which is actively used for water transportation activities and domestic and international cruise, container loading and unloading, the fishing industry, and water sports activities. To support the development of activities in the area, continuous maritime observation data is needed. BMKG as a national meteorological agency installed an automatic weather station (AWS) around the Benoa Port area, so that maritime observation data can be collected and processed further. The maritime AWS at the Benoa Port is also equipped with sensors that can measure water level. This study uses water level data to determine the type of tides at the Benoa port by using the Admiralty method. The results of this study indicate that the tidal type at Benoa port is a mixed tide prevailing semidiurnal. It is hoped that the results of this study can be useful and become a reference for further research.